Successful treatment of normocomplementemic urticarial vasculitis with omalizumab: A report of three cases and literature review - Teerapong Rattananukrom (2021)
Urticarial vasculitis (UV) is a rare form of cutaneous leukocytoclastic vasculitis with persistent urticarial lesions. UV may be severe and refractory to standard treatment including antihistamines, anti-inflammatories, antimalarials, corticosteroids and immunosuppressants. Omalizumab, an anti-IgE antibody, is approved for chronic spontaneous urticaria. However, its benefit for UV remains controversial. We report, herein, three patients with normocomplementemic UV and angioedema. All patients were diagnosed with chronic urticaria preceding the presentation of painful urticarial plaques. The diagnosis of UV was confirmed by skin biopsy and/or direct immunofluorescence. All patients had none or minimal response to standard treatments. Initial omalizumab dosing of 150 mg was administered subcutaneously (SC), however, increment to 300 mg monthly was necessary in 2 patients to control the disease. All 3 patients remained in complete remission after minimum follow up period of 9 months. To conclude, omalizumab has shown to be beneficial for severe normocomplementemic UV in our series.